Influences of acceptor dopants (Cu, Mg, Fe) on electrical and optical properties of Ba0.7Ca0.3TiO3 ceramics - Panupong Jaiban (2019)
© 2019 Elsevier Ltd Ba0.7Ca0.3TiO3 (BCT) ceramics with different dopants, including Fe3+, Mg2+, and Cu2+ ions, were prepared by a solid-state sintering method. All doping elements induced a change in the crystal structure and microstructure of BCT ceramics. The dielectric, ferroelectric and piezoelectric properties of the doped ceramics were observed in a correlation between the phase fraction and difference in grain size. The decrease of grain size indicated a surface enhancement in an ultraviolet light response of doped ceramics. The recovering rate of resistivity of all ceramics after removing the light depended on dopants. The results here suggested that microstructural variation could be useful for tuning both the electrical properties and ultraviolet light-induced conductivity of perovskite materials which may find future application in optoelectronic and electronic devices.